Dental Service Utilization and Barriers to Dental Care for Individuals with Autism Spectrum Disorder in Jordan: A Case-Control Study - Sabha Mahmoud Alshatrat; Isra Abdelkarim Al-Bakri; Wael Mousa Al-Omari (Hindawi Limited, 2020)
Individuals with disabilities are at higher risk for oral diseases such as caries and periodontal disease. Therefore, regular dental care is essential to maintain oral health. However, individuals with disabilities encounter difficulties in accessing dental care. The challenges and barriers to oral care faced by individuals with autism spectrum disorder (ASD) have not been addressed in Jordan. The aim of this study was to examine the use of dental services in individuals with ASD in Jordan and identify barriers that affect their access to dental care in comparison with individuals without ASD. A case-control study was carried out among 296 parents/caregivers of individuals with ASD and individuals without ASD, which involved completion of a self-designed questionnaire. The majority of the participants in both groups had visited the dentist in the year preceding completion of the questionnaire. The main reason for visiting dental services was toothache (43%), and the least common reason was routine checkup (11.6%), with a significant difference (P<0.05) observed between the two groups. Barriers including embarrassment (43.5%), a lack of specialized dental staff (28.6%), a lack of knowledge of how to treat people with disabilities (26.6%), and inadequate facilities (34%) were significantly (P<0.05) more likely to be reported by individuals with ASD than the controls. In conclusion, knowing and understanding the barriers to accessing dental care could improve overall health for individuals with ASD. Furthermore, recognizing the challenges in accessing dental care for this population could help oral health professionals to minimize these difficulties.